Selling Virtual Currency in Digital Games: Implications for Gameplay and Social Welfare - Guo, Hong; Hao, Lin; Mukhopadhyay, Tridas; Sun, Daewon (Information Systems Research, 2019)
The sale of virtual currency has become an important revenue source in the digital gaming industry. This paper analyzes the impact of this business model on players’ gaming behavior, the game provider’s strategies for virtual currency price and ad level, and social welfare. Our findings have important managerial implications for the gaming industry and policy makers. We find that when the enabling-power rate of virtual currency (i.e., how much players benefit from enhanced gameplay due to virtual currency generated per unit of playing time) is stronger, players have lower incentive to purchase virtual currency. Therefore, the provider should set a lower price to avoid losing too much demand. In the meantime, the marginal benefit of playing the game increases, and thus the provider should set a higher ad level to take advantage of this boosted marginal benefit for players when the base valuation of gameplay is sufficiently low. Finally, we demonstrate that offering in-game purchases of virtual currency as a new business model benefits society as a whole. Our findings suggest that regulators of the gaming industry should be less concerned about the risk of excessive gameplay for games that sell virtual currency compared with those that do not.